FEATURES OF THE DIFFERENTIATED APPROACH TO PROFESSIONAL TRAINING OF THE FUTURE PHYSICAL CULTURE TEACHER - Nurmatov Bahrom Bektemirovich (Galaxy International Interdisciplinary Research Journal, 2023)
The article defines the role of the differentiated approach in the training of the future physical culture teacher and establishes the pedagogical conditions for its implementation in the process of teaching gymnastics.